2021
DOI: 10.3390/metabo11090604
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolite Profile Associated with Sex-Dependent Visceral Adiposity Index and Low Bone Mineral Density in a Mexican Population

Abstract: Recent evidence shows that obesity correlates negatively with bone mass. However, traditional anthropometric measures such as body mass index could not discriminate visceral adipose tissue from subcutaneous adipose tissue. The visceral adiposity index (VAI) is a reliable sex-specified indicator of visceral adipose distribution and function. Thus, we aimed to identify metabolomic profiles associated with VAI and low bone mineral density (BMD). A total of 602 individuals from the Health Workers Cohort Study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
2
3
0
Order By: Relevance
“…An evolving body of epidemiological studies supports that amino acids could influence bone turnover regulation [16][17][18][19][20][21][22]. While essential amino acids, including BCAA, could play a beneficial role stimulating osteoblast growth, AAA could promote osteoclast activity and bone resorption [20,21], which is overall consistent with our findings.…”
Section: Amino Acidssupporting
confidence: 90%
See 1 more Smart Citation
“…An evolving body of epidemiological studies supports that amino acids could influence bone turnover regulation [16][17][18][19][20][21][22]. While essential amino acids, including BCAA, could play a beneficial role stimulating osteoblast growth, AAA could promote osteoclast activity and bone resorption [20,21], which is overall consistent with our findings.…”
Section: Amino Acidssupporting
confidence: 90%
“…In cross-sectional studies from Australia [16] and China [18], a null association between serum and dietary AAA with central BMD was reported. Inconsistently with our findings, two studies -from Mexico (N = 602) and China (N = 2997)-reported a positive association of leucine levels and reduced BMD [19] and an inverse association between tryptophan and reduced BMD [21].…”
Section: Amino Acidssupporting
confidence: 76%
“…Concentrations of forty serum metabolites (ACs, free carnitine (AC0), and amino acids) were measured using the approach of targeted metabolomics as previously described [36]. NeoBase MSMS kit is intended for the quantitative determination of ACs: Free carnitine (AC0), Acetyl acylcarnitine (AC2), Propionyl acylcarnitine (AC3), Butyryl acylcarnitine (AC4), Isovaleryl acylcarnitine (AC5), Tiglyl acylcarnitine (AC5:1), Hexanoyl acylcarnitine (AC6), Adipoyl acylcarnitine (AC6DC), Octanoyl acylcarnitine (AC8), Octenoyl acylcarnitine (AC8:1), Hexadecanoyl acylcarnitine (AC16), Hexadecenoyl acylcarnitine (AC16:1), Hydroxy Hexadecenoyl acylcarnitine (AC16:1OH), Hydroxy Hexadecanoyl acylcarnitine (AC16OH), Decanoyl acylcarnitine (AC10), Decenoyl acylcarnitine (AC10:1), Decadienoyl acylcarnitine (AC10:2), Dodecanoyl acylcarnitine (AC12), Dodecenoyl acylcarnitine (AC12:1), Tetradecanoyl acylcarnitine (AC14), Tetradecenoyl acylcarnitine (AC14:1), Tetradecadienoyl acylcarnitine (AC14:2), Hydroxy tetradecenoyl acylcarnitine (AC14OH), Octadecanoyl acylcarnitine (AC18), Octadecadienal acylcarnitine (AC18:1), Hydroxy octadecenoyl (AC18:1OH), Octadecadienal acylcarnitine (AC18:2), and Hydroxy octadecanoyl (AC18OH); amino acids: Glycine, Alanine, Valine, Leucine, Methionine, Phenylalanine, Tyrosine, Ornithine, Citrulline, Arginine, and Proline; and the ketone Succinylacetone.…”
Section: Targeted Metabolomics Analysismentioning
confidence: 99%
“…Our findings that higher valine to phenylalanine and lower glycine to alanine ratios were inversely associated with fracture are supported by prior research ( 9 ) which found that higher plasma levels of valine and alanine were negatively associated with osteoporosis in women. Similarly, in the female population, higher glycine levels were associated with lower BMD ( 24 ). Methionine was demonstrated to enhance osteoblast proliferation, activation, differentiation and BMD ( 25 , 26 ), which is in line with our study finding that the ratio of methionine to phenylalanine is negatively associated with fracture.…”
Section: Discussionmentioning
confidence: 98%